Powder X-ray diffraction of 1-(4-Nitrophenyl)-2-piperidinone, C11H12N2O3. Issue 4 (13th August 2015) - Wang, Qing; Xiong, Xin Nuo; He, Jia Wei; Tang, Pei Xiao; Li, Hui
Abstract : X-ray powder diffraction data for 1-(4-Nitrophenyl)-2-piperidinone, C11 H12 N2 O3, are reported [ a = 9.514(3) Å, b = 12.308(6) Å, c = 9.175(1) Å, α = 90°, β = 91.811(2)°, γ = 90°, V = 1073.94 Å 3, Z = 4, ρ cal = 1.362 g cm −3 and space group P 21 /n]. All measured lines were indexed and are consistent with the P 21 /n space group. No detectable impurities were observed.